37. ASSESSMENT OF COMMUNICATION SKILLS AMONG HEALTHCARE STAFF AT HOAN MY GENERAL HOSPITAL DA LAT (Vietnam Journal of Community Medicine, 2025)
Introduction: In the clinical setting, professional communication among healthcare staff is a crucial tool for information transfer and a foundation for effective collaboration in patient care. Physicians and nurses are the two core forces in the treatment process, each playing distinct roles but relying on each other for medical decision-making and intervention implementation.Objective: To assess clinical physicians' and nurses' communication and interpersonal skills in professional practice at Hoan My General Hospital Da Lat.Subjects and methods: A cross-sectional descriptive study was conducted using a structured questionnaire through interviews. The study included all medical staff, comprising 45 physicians and 145 nurses, from June 2024 to January 2025.Results: The average age was 28.5 years; average working experience was 5.5 years. The frequency of speaking loudly and giving direct commands at the "rarely" level accounted for 47.8% and 63.1%, respectively; the "rarely" level was 34% and 27.8%, respectively. Nurses reported communicating with physicians regarding patient conditions (99.3%), infrastructure (17.2%), treatment plans (89.6%), and patient care plans (96.5%). Physicians reported communicating with nurses regarding patient conditions (97.7%), infrastructure (33.3%), treatment (93.3%), and patient care plans (95.5%); other topics were reported at 13.1% and 22.2%, respectively. In our study, 185 out of 190 respondents (97%) agreed or strongly agreed on the need for an anonymous channel to share communication difficulties. 89.4% agreed on the necessity of standardized communication and behavior tools within the hospital; 2.1% had no opinion. Monthly training sessions and workshops to address communication concerns received 46.8% complete agreement and 12.6% no opinion. For training on communication and interaction scenarios during teamwork, 123 respondents (64.7%) strongly agreed, while 11 respondents (5.7%) had no opinion. Conclusion: Overall, communication skills between physicians and nurses were practical, with a high professional exchange rate and positive satisfaction. The study results serve as an essential foundation for developing appropriate training programs to improve interdisciplinary collaboration and the quality of medical care.
Keywords: Communication skills; healthcare staff; Hoan My Hospital.